2021
DOI: 10.1371/journal.pone.0248920
|View full text |Cite
|
Sign up to set email alerts
|

App-based symptom tracking to optimize SARS-CoV-2 testing strategy using machine learning

Abstract: Background Tests are scarce resources, especially in low and middle-income countries, and the optimization of testing programs during a pandemic is critical for the effectiveness of the disease control. Hence, we aim to use the combination of symptoms to build a predictive model as a screening tool to identify people and areas with a higher risk of SARS-CoV-2 infection to be prioritized for testing. Materials and methods We performed a retrospective analysis of individuals registered in "Dados do Bem," a Bra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…The results also show that the symptoms experienced by C19+ significantly differ, except for dyspnea, to those experienced by C19−. This agrees with other studies that also reported hyposmia, dysgeusia, and fever as significantly increased in C19+ persons [ 6 , 21 , 22 ]. Further, the large relative difference of hyposmia (+155%) and dysgeusia (+101%) frequencies for C19+ in comparison to C19− users suggests that hyposmia and dysgeusia are specific but not sensitive, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The results also show that the symptoms experienced by C19+ significantly differ, except for dyspnea, to those experienced by C19−. This agrees with other studies that also reported hyposmia, dysgeusia, and fever as significantly increased in C19+ persons [ 6 , 21 , 22 ]. Further, the large relative difference of hyposmia (+155%) and dysgeusia (+101%) frequencies for C19+ in comparison to C19− users suggests that hyposmia and dysgeusia are specific but not sensitive, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The function generates a Health Code associated with different colors (green, yellow, red) based on the risk of being infected [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The app Dados do Bem was developed in Brazil to track COVID-19 symptoms: applying machine learning techniques, it was possible to provide a SARS-CoV-2 infection risk map of the city of Rio de Janeiro, representing a potential tool for decision-makers to refine disease-control strategies [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Digital screening tools are also in development to track COVID-19 symptoms and support the identification of infection. In Brazil, where testing resources are limited, an app-based symptom tracker has been developed to help prioritize those who should be tested [ 89 ]. After implementation of the app, the proportion of positive results increased significantly from 14.9% to 18.1%.…”
Section: Different Testing Settingsmentioning
confidence: 99%